Analysis of Bacteriophage φ29 Gene Function: Protein Synthesis in Suppressor-Sensitive Mutant Infection of Bacillus subtilis - Anderson, Dwight L. (1974)
Phage φ29 suppressor-sensitive (sus) mutants of 14 cistrons have been examined for production of (14)C-labeled viral-specific proteins in restrictive infections of Bacillus subtilis. Proteins specified by four cistrons (H, J, L, and N) have been resolved and identified by sodium dodecyl sulfate gel electrophoresis and autoradiography, and fragments of the normal polypeptides were detected. Mutants of six cistrons (C, D, E, F, I, and M) demonstrated two or more missing bands in the gel profiles, and thus some of these gene products may have regulatory functions. Mutation was detected in at least five genes coding for low-molecular-weight proteins, but a conditionally lethal mutant in only one of these genes has been isolated. Preliminary evidence that a precursor protein is cleaved to generate the neck appendage structural protein and a low-molecular-weight product has been obtained.